Pengembangan Materi Ajar Digital Berbasis CTL Terintegrasi Nilai Islam untuk Pendidikan Pancasila di SDIT - Raisya Andre Pandoe; Arwin (Suria Academic Press, 2025)
Learning of Pancasila Education in elementary schools remains insufficiently contextual and lacks the utilization of digital media; therefore, it is necessary to develop CTL-based teaching materials integrated with Islamic values to foster students’ national and religious character. This study aims to develop and examine the feasibility of Digital Teaching Materials for Pancasila Education based on the Contextual Teaching and Learning (CTL) approach integrated with Islamic values for Grade IV students at Integrated Islamic Elementary Schools (SDIT). The research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects included teachers and Grade IV students from four SDIT in Padang City: SDIT Arafah, SD Islam Nibros, SDIT Cendekia Andalas, and SDIT Permata. Research instruments consisted of validation sheets for material experts, media experts, and language experts, as well as practicality questionnaires for teachers and students, and learning outcome tests (pretest–posttest). The results showed that the developed product was categorized as highly valid with an average score of 93%, highly practical with a score of 93.5%, and effective in improving students’ learning outcomes with an N-Gain score of 0.75 (high category). Learning using CTL-based digital teaching materials was proven to enhance student engagement, understanding, and character formation, particularly in instilling the values of unity, ukhuwah (brotherhood), ta’awun (mutual help), and amanah (responsibility). Thus, the CTL-Based Digital Teaching Materials for Pancasila Education Integrated with Islamic Values are declared valid, practical, and effective as an innovative instructional resource for Pancasila Education in integrated Islamic elementary schools. This product is expected to serve as a reference for developing contextual and character-based digital learning media in the era of the Kurikulum Merdeka.